Galanin inhibits GLP‐1 and GIP secretion via the GAL1 receptor in enteroendocrine L and K cells. (8th February 2016) - Psichas, Arianna; Glass, Leslie L; Sharp, Stephen J; Reimann, Frank; Gribble, Fiona M
Abstract : Background and Purpose: Galanin is a widely expressed neuropeptide, which in the gut is thought to modulate gastrointestinal motility and secretion. We aimed to elucidate the poorly characterised mechanisms underlying the inhibitory effect of galanin and the potential involvement of G‐protein coupled inwardly rectifying potassium, Kir 3, (GIRK) channels in glucagon‐like peptide 1 (GLP‐1) and glucose‐dependent insulinotropic polypeptide (GIP) secretion. Experimental Approach: Purified murine L and K cells were analysed for expression of galanin receptors and GIRK subunits. Hormone secretion was measured from primary murine intestinal cultures. Intracellular cAMP was monitored in primary L cells derived from mice expressing the Epac2camps sensor under the control of the proglucagon promoter. Key Results: Galanin receptor 1 (GAL1, Galr1 ) and GIRK channel 1 (Kir 3.1, Kcnj3 ) and 4 (Kir 3.4, Kcnj5 ) mRNA expression was highly enriched in K and L cells . Galanin and a selective GAL1 receptor agonist (M617) potently inhibited GLP‐1 and GIP secretion from primary small intestinal cultures. In L cells, galanin significantly inhibited the forskolin‐induced cAMP response. The GIRK1/4 activator ML297 significantly reduced glucose‐stimulated and IBMX‐stimulated GLP‐1 secretion but had no effect on GIP. The GIRK blocker tertiapin‐Q did not impair galanin‐mediated GLP‐1 inhibition. Conclusions and Implications: Galanin, acting via the GAL1 receptor and Gi ‐coupled signalling in L and K cells, is a potent inhibitor of GLP‐1 and GIP secretion. Although GIRK1/4 channels are expressed in these cells, their activation does not appear to play a major role in galanin‐mediated inhibition of incretin secretion.